Catalytic Degradation of Rhodamine B over FeMCM-41 - Nookaraju, M.; Rajini, A.; Venkatathri, N.; Ajit Kumar Reddy, I. (Asian Journal of Chemistry, 2012)
Fe incorporated MCM-41 (FeMCM-41) is synthesized at room temperature by instant mixing of silica and iron precursors to a clear solution of surfactant following co-precipitation method. It is characterized by various physico-chemical techniques like PXRD, BET, FT-IR and SEM. The mesoporous character of the material has been established from BET adsorption desorption studies. Degradation Rhodamine B in presence of hydrogen peroxide as oxidant over FeMCM-41 has been investigated. It is observed that 94.25 % of dye gets degraded in 150 min. It is found that degradation % increases with increase in pH and also with increase in the concentration of oxidant. Optimum conditions for the degradation of Rhodamine B by hydrogen peroxide over FeMCM-41 have been established.